Nanofiltration and reverse osmosis as a platform for production of natural botanic extracts: the case study of carob by-products - Almanasrah, Mohammad (2016)
Carob kibbles are a low-cost and renewable source of economically relevant phenolic compounds (high value catechin and its derivatives and gallic acid) and abundant in small sugars. This work aims at producing two distinct natural extracts from carob kibbles, one extract enriched in catechin and its derivatives for the nutraceuticals market and an extract enriched in sugars for the food industry. This valorisation strategy involves an integrated process based on membrane technology that fulfils the zero discharge principle and may be applied to other agro-industrial by-products. Different aqueous extraction schemes were considered (a one-step process and a two-steps approach). The aqueous extracts obtained were fractionated by diananofiltration and the fractions obtained were evaluated in terms of their content in target products. An integrated scheme for production of fractionated extracts is proposed based on the experimental work developed assuring, simultaneously, a minimal use of resources and emission of waste.